PENGEMBANGAN OLAHAN TAHU DAN LIMBAHNYA BERBASIS TEKNOLOGI PENGAWETAN MENUJU DIVERSIFIKASI PRODUKSI PASCA ERUPSI - dan Mutiara Nugraheni, Rizqie Auliana, Siti Hamidah, Fitri Rahmawati, (Universitas Negeri Yogyakarta, 2013)
Activities aim to: (1) improve knowledge of the impact of wastepollution targets tofu production and utilization, (2) increasing knowledgeabout the application of technology preservation objectives in the utilizationof know and disposal, (3) improve the skills targeted in developing wasteprocessing technology know and preservation (freezing, drying, and fermentation)into nuggets knows, flour tofu, tofu crackers, soy tofu and natade soya, and (4) improve skills in applying technology targets packaging.What activities are Ngasem Hamlet Village Sindumartani NgemplakSleman district. Model form of training activities to target as many as 35people representing housewife dasa homestead. In the training conductedfrom August to September 2012. Implementation of training six times faceto face with the details: (1) continued opening theory about the impact ofwaste processed tofu and development of technology-based preservation, (2)processing tofu crackers, (3) processing soy tofu, (4) processing of nata desoya, (5) processing nugget tofu and tofu flour and (6) packaging productsand evaluation of results.The results showed that the implementation of the training objectiveshave the knowledge, skills and good response. This is supported also by theamount of face-to-face attendance at each show more than 75% attendance.86.7% target already has a good level of knowledge prior to training andincreasing to 100% after training. With medium and high categories. Thusthe goal was to understand the material being taught and understand theimpact and utilization of waste out through simple preservation technology.The results of the evaluation of the target skills also have shown success. Itis seen if the lowest value obtained is 78 which means it exceeds the valueof the lowest standard 70. Evaluation of these skills included in thepackaging. Thus, the leading PPM goals set have been achieved all goodknowledge and skills. The results of the evaluation of a given targetresponse showed that 30% target stated it useful and 70% said veryrewarding.